Sim Kie Chon V. Superintendent Of Pudu Prison & Ors: The Royal Prerogative Of Mercy? - Crook, Peter (Journal of Malaysian and Comparative Law, 2019)
The power of the Yang di-Pertuan Agong to grant pardons is found in Article 42 of the Federal Constitution and Regulation 29 of the Essential (Security Cases) Amendment Regulations 1975, as amended in 1981 (ESCAR). Until recently the pardon power had not attracted much judicial attention. This, however, changed dramatically in 1985. In perhaps the most controversial case of the year, Sim Kie Chon, a prisoner awaiting execution, challenged the denial by the Pardons Board of his application for pardon as a violation of equal protection of the law guaranteed by Article 8(1) of the Federal Constitution.